Strategi Pemasaran Multilevel Marketing Dalam Menghadapi Tantangan Global - Delia, Dwi Anisa; Zakir, Muhammad (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
This research aims to examine the transformation of Multi Level Marketing (MLM) marketing strategies in facing global challenges caused by developments in digital technology, changes in consumer behavior and globalization. In this context, this research focuses on how MLM companies adapt and implement new marketing strategies to remain relevant and competitive. The research method used is a qualitative method with a case study approach. Data was collected through in-depth interviews with executives, marketing managers, and main distributors from several different MLM companies. In addition, content analysis was carried out on the digital marketing materials used by these companies. Data analysis was carried out using thematic analysis techniques to identify main patterns and themes that emerged from the data. The research results show that MLM companies that are successful in transforming their marketing strategy tend to integrate digital technology such as social media, mobile applications and e-commerce platforms in their operations. Additionally, they emphasize transparency and building trust with customers and distributors through open and honest communication. This research also found that adapting to local needs and preferences is very important in global marketing strategies. Innovation in products and services as well as compliance with regulations and business ethics are key factors that support the successful transformation of MLM marketing strategies.